IMPROVING UNIVERSAL PRECAUTIONS KNOWLEDGE THROUGH VIRTUAL CARE REALITY VIDEO 360° IN PPROFESSIONAL NURSE PROGRAM STUDENTS - Triyanto, Endang; Jauhar, Muhamad; Rohana, I Gusti Ayu Putu Desy; Kusumawardani, Lita Heni; Choiruna, Hasby Pri; Setiyowati, Erni; Rasdiyanah, Rasdiyanah; Rachmawati, Utami (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Current learning methods are constantly evolving. Professional Nurse Program Students need effective learning methods to improve students’ abilities and skills in achieving competencies, and one of the competencies is standard precautions. Virtual care reality video3600 can be an alternative solution for students’ actual and concrete learning methods. This study aims to determine the effect of Virtual care reality video3600 on the standard precautions knowledge of Professional Nurse Program Students.           Methods: The Research design uses a quasi-experimental pre-post test with the control group. The research sample consists of 38 students for the intervention group and 32 students for the control group. The research site was at Jenderal Sudirman University and the University of Indonesia in June-September 2022. The research instrument uses a standard precaution knowledge questionnaire. Researchers provide virtual care reality video3600 interventionfor 17 minutes at least three times in each video. VCR 3600 contains material on standard precautions consisting of proper hand washing, Personal Protective Equipment (PPE) use, safe injection practices, and handling of potentially contaminated equipment or surfaces in the patient's environment. Post-test measurement is carried out two weeks after the intervention. Data analysis uses paired t-tests and independent t-tests.   Results: The results showed that the age of the respondents was between 21-31 years old, with a median value of 22 years. The gender respondents were mostly women, the majority of respondents had never been nurses, the majority of respondents had studied infection control, most of the respondents had not received the Hepatitis B vaccine, and the majority of respondents had never reported the incidence of needle sticks. The statistical test results obtained a significant change in knowledge (p-value = 0.001).  Conclusions: The results showed a significant increase in respondents’ knowledge level after the intervention. The research results are expected to be applied in the learning process of Professional Nurse Programs in universities. In addition, it is hoped that the VCR 3600 method can be used for other Professional Nurse Program learning themes.Keywords: standard precaution; video 3600 ; virtual care reality